Community Health Worker (CHW) Training Effects on Prisons - Logue, Shawna (Kansas State University. Dept. of Sociology, Anthropology, and Social Work., 2025)
Community Health Workers (CHWs) are a new concept to the state of Kansas, with the Kansas CHW Coalition being founded in 2022 (Rankin, 2022). CHWs impact the communities that they serve by case management services that help their clients find resources and education, plus gain confidence, which as a workforce development program that could help to change the way that the Kansas prison system works. The wardens of this system have certain motivations for implementing programs. The main research questions are what motivates wardens to implement a program like the CHW program and what is the impact of CHWs on the prison and how do the wardens view this impact. This study will show the impact that CHWs have and what will motivate the 4-5 wardens who participate in the Zoom interviews in this study to want to have a CHW training program as a part of their rehabilitation program for the incarcerated individuals in their prisons. Patterns in what they need and what motivates them to want to implement new programs will be studied. The impact of the CHW training program can improve the prison system on the micro and macro levels of a system theory. This could possibly lead to other workforce programs becoming a regular part of the rehab of those that are serving time in the Kansas prisons.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: Community Health Workers (CHWs); Kansas CHW Coalition; Prisons; Workforce Programs; Kansas Prison System Reform